Unilateral emission reductions can lead to Pareto improvements when adaptation to damages is possible - Klaus Eisenack; Leonhard Kähler (University of Oldenburg, Department of Economics, 2012)
Policy advocates frequently request for unilateral action to push forward climate protection in international negotiations. It is yet conventional wisdom in environmental economics that unilateral action does not pay for the first mover due to free-riding behavior of the other countries. How does this analysis change if there is a further option at hand: off-setting damages from joint emissions by individual adaptation measures? Adaptation to climate change plays an increasingly role in the international negotiations under the UNFCCC. This paper shows that when adaptation is considered as an explicit decision variable, and unilateral action is framed as a Stackelberg game, the resulting convexity properties imply (when the follower has a specific property) that total emissions are reduced to the benefit of all countries in the game equilibrium. When countries play a game of timing in a period before emission and adaptation decisions - to determine who takes the role of the Stackelberg leader - it is shown that a country with this specific property indeed becomes the follower. The equilibrium of the overall game is Pareto superior to the non-cooperative Nash solution.
Keywords: 330; international environemental problems; climate change; Stackelberg game; convexity